2021
DOI: 10.1002/ajh.26440
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood viscosity and red blood cell aggregation in patients with COVID‐19

Abstract: The aim of this study was to ( 1) analyze blood viscosity, red blood cell (RBC) deformability, and aggregation in hospitalized patients with Coronavirus disease 19 (COVID-19); (2) test the associations between impaired blood rheology and blood coagulation; and (3) test the associations between impaired blood rheology and several indicators of clinical severity. A total of 172 patients with COVID-19, hospitalized in COVID-unit of the Internal Medicine Department (Lyon, France) participated in this study between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 51 publications
4
58
2
5
Order By: Relevance
“…RBC aggregation represents another crucial rheological parameter which was described to be affected by acute severe COVID-19 disease. 12,39 The present data could not support these findings, possibly because of the mild nature of the disease course reported herein or because the enrolled subjects did not show additional diseases which were described for the COVID-19 patients by Renoux and colleagues. 12 Though, shear rate balancing aggregation and disaggregation was remarkably higher in the COVID-19 groups and it seems plausible that the membrane evaginations and elongation of the cells described earlier increase the contact area between adjacent RBC thus increasing forces connecting these cells.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…RBC aggregation represents another crucial rheological parameter which was described to be affected by acute severe COVID-19 disease. 12,39 The present data could not support these findings, possibly because of the mild nature of the disease course reported herein or because the enrolled subjects did not show additional diseases which were described for the COVID-19 patients by Renoux and colleagues. 12 Though, shear rate balancing aggregation and disaggregation was remarkably higher in the COVID-19 groups and it seems plausible that the membrane evaginations and elongation of the cells described earlier increase the contact area between adjacent RBC thus increasing forces connecting these cells.…”
Section: Discussioncontrasting
confidence: 78%
“…Since RBC deformability is crucial for the passage of the small capillaries and oxygen supply within the microcirculation, it is suspected that stiffening of RBC, next to haemoglobin alterations, might also be associated to the described hypoxemia 38 during COVID‐19 infection. RBC aggregation represents another crucial rheological parameter which was described to be affected by acute severe COVID‐19 disease 12,39 . The present data could not support these findings, possibly because of the mild nature of the disease course reported herein or because the enrolled subjects did not show additional diseases which were described for the COVID‐19 patients by Renoux and colleagues 12 .…”
Section: Discussioncontrasting
confidence: 74%
“…For example, in septic conditions membrane SA concentration tends to decrease, which leads RBC to become spherical and to decrease their intercellular repulsion; these variations tend to increase blood viscosity and this finding constitutes one of the pro-coagulant elements which can be encountered in these patients. 226 Analogue morphologic changes of the whole cell may occur in many more tissues: this phenomenon depends upon the milieu pH, the membrane potential charge, the concentration and conformation of the receptors, which also influence the osmotic gradient. 98 b) CD147 Together with SA, also CD147 transmembrane receptor glycoprotein plays a role in COVID-19 pathogenicity.…”
Section: A) Sialic Acidmentioning
confidence: 99%
“…It is known that oxygen therapy promotes oxidation of membrane lipids, as shown by increased hydroperoxide values in the erythrocyte membrane of preterm infants exposed to oxygen therapy, 4 and that erythrocyte viscosity and aggregation are increased in patients with COVID-19 who require oxygen supplementation. 5 The changes in erythrocyte viscosity and aggregation are largely mediated by increased fibrinogen, suggesting that they may be secondary to hypercoagulability and vascular changes associated with pulmonary lesions. 5 Studies in patients with type 1 diabetes mellitus and who were exposed to hyperbaric oxygen showed decreased iNOS activity and/or expression in lymphocytes and increased plasma arginase activity, 6 which suggested that a NO-restricted state could be a consequence of oxygen therapy.…”
mentioning
confidence: 99%
“… 5 The changes in erythrocyte viscosity and aggregation are largely mediated by increased fibrinogen, suggesting that they may be secondary to hypercoagulability and vascular changes associated with pulmonary lesions. 5 Studies in patients with type 1 diabetes mellitus and who were exposed to hyperbaric oxygen showed decreased iNOS activity and/or expression in lymphocytes and increased plasma arginase activity, 6 which suggested that a NO-restricted state could be a consequence of oxygen therapy.…”
mentioning
confidence: 99%